On the glide of [100] dislocation and the origin of 'pencil glide' in Mg2SiO4 olivine. Issue 22 (17th November 2019) - Mahendran, S.; Carrez, Ph.; Cordier, P.
ABSTRACT: Olivine with chemical composition (Mg, Fe)2 SiO4 is a silicate which is supposed to strongly constrain the flow of the Earth's upper mantle under thermal convection. Its mechanical properties are thus of primary importance. Slip systems in olivine involve two types of dislocations with [100] and [001] Burgers vectors. In this study, we report atomistic modelling of screw dislocations with [100] Burgers vector and their intrinsic properties. We show that the [100] screw dislocation core exhibits several configurations corresponding to spreading in different planes and different relative stabilities. At low pressure, we identify a clear tendency for core spreading in (010). At higher pressure, relevant for the Earth's mantle, we show that pressure promotes a change in core configuration with spreading into equivalent {021} planes. Based on the systematic investigation of the minimum energy path between the different configurations, we show that the variability of core structures allows complex glide paths which has been described at the macroscopic level as 'pencil glide'. Our results suggest that the pencil glide is more efficient at high pressure.